The Role of Nasyiatul Aisyiyah and Fatayat NU Cadres in Preventing Stunting Cases in Indonesia - Bekti Handayani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Stunting is a growth disorder caused by a lack of nutritional intake in toddlers. The factors that cause stunting in developing countries are not giving exclusive breastfeeding, socio-economic constraints, lack of mother's knowledge, and infectious diseases to poor environmental sanitation. The role of Nasyiatul Aisyiyah dan Fatayat NU cadres is needed to eliminate the stunting case in Indonesia. This article is aimed to elaborate on the role of Nasyiatul Aisyiyah and Fatayat NU to decrease stunting cases in Indonesia. This article uses a literature study research method by analyzing the role of Nasyiatul Aisyiyah dan Fatayat NU in Indonesia. In this article, it is stated that Nasyiatul Aisyiyah cadres actively prevent stunting by having the Nutrition House program which is one of the community-based models as an effort to develop food sovereignty and security. Meanwhile, Fatayat NU increases the involvement of community leaders in advocacy, communication, information, and education on family planning, also known as the Proud Kencana program. Thus, the role of Nasyiatul Aisyiyah and Fatayat NU cadres has made a positive contribution in preventing stunting cases in Indonesia.